Hepatitis B vaccination status among healthcare workers in a tertiary care hospital in Tripoli, Libya - Hisham Ziglam; Mabrouk El-Hattab; Noura Shingheer; Abdulaziz Zorgani; Omar Elahmer (Elsevier, 2013)
Summary: Background: The prevalence of hepatitis B virus (HBV) among healthcare workers (HCWs) in hospitals in developing countries is high. However, the vaccination status of these workers and its relationship with occupational factors are not well documented. Aim: The aim of this study was to evaluate the susceptibility of HCWs to HBV infection in the representative Tripoli Central Hospital in Libya and prepare a practical guideline to protect HCWs from occupational exposure. Method: In this cross-sectional study, a questionnaire survey was administered to 2705 healthcare workers of a university hospital in Tripoli. The questionnaire included vaccination status. Compliance with preventive practices against HBV infection was also assessed. Result: The overall vaccination coverage (anti-HBs) was 78.1%. Furthermore, 82.6% of HCWs had received at least one dose of vaccine, but only 72% reported that they were fully vaccinated. The prevalence of hepatitis B surface antigen was 1.1%. The mean prevalence of hepatitis B core antibody (anti-HBc) was 17.3%. Conclusion: HCWs at hospitals are frequently exposed to blood-borne infections. Vaccines should be more readily available for Libyan HCWs, and current vaccination programs should be enforced. Keywords: Hepatitis B vaccination, HBsAb titer, Health care worker